Vitamin D status & associations with inflammation in older adults - Bourke, Nollaig; O'Halloran, Aisling; Kenny, Rose (My University, 2023)
Research studies have observed associations of vitamin D with inflammation but data in representative older adult studies is lacking. We aimed to investigate the association of C-reactive protein (CRP) with vitamin D status in a representative sample of the older Irish population. The concentrations of 25-hydroxyvitamin D (25(OH)D) and CRP was measured in 5,381 community dwelling Irish adults aged ≥50 years from the Irish Longitudinal Study on Ageing (TILDA). Demographic, health and lifestyle variables were assessed by questionnaire and categorical proportions of CRP were generated by vitamin D status and age. Multi-nominal logistic regression was used to investigate the association of 25(OH)D and CRP status. The prevalence (mean; 95% confidence interval (95% CI)) of normal CRP status (0-5 mg/dL) was 83.9% (82.6-85.0%), elevated status (5-10 mg/dL) 11.0% (9.9-12.0%) and high status (>10 mg/dL) was 5.1% (4.5-5.8%). Mean (95% CI) CRP concentrations were lower in those with normal vs. deficient 25(OH)D status (2.02 mg/dL (1.95-2.08) vs. 2.60 mg/dL (2.41-2.82); p<0.0001). In a logistic regression analysis, those with insufficient or sufficient 25(OH)D status were less likely to have a high CRP status compared to those with deficient 25(OH)D status (insufficient: coefficient (CE) -0.732, 95% CI -1.12-0.33, p<0.0001; sufficient: CE -0.599, 95% CI -0.95-0.24, p = 0.001). In conclusion older adults with deficient vitamin D status had higher levels of inflammation as measured by CRP. Given that inflammation is an important pathological driver of chronic diseases of ageing, and that emerging evidence suggests that vitamin D therapy can reduce inflammation in some disease settings, optimising vitamin D status could represent an effective low risk/low-cost pathway to modulate inflammation in community dwelling older adults.
PLoS One
PUBLISHED
Keywords: Ageing